2016
DOI: 10.1016/j.ygyno.2016.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of endometrial carcinoma on diagnostic specimens is highly concordant with final hysterectomy: Earlier prognostic information to guide treatment

Abstract: Objective Categorization and risk stratification of endometrial carcinomas is inadequate; histomorphologic assessment shows considerable interobserver variability, and risk of metastases and recurrence can only be derived after surgical staging. We have developed a Proactive Molecular Risk classification tool for Endometrial cancers (ProMisE) that identifies four distinct prognostic subgroups. Our objective was to assess whether molecular classification could be performed on diagnostic endometrial specimens ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 35 publications
5
123
0
1
Order By: Relevance
“…This series of 49 cases showed, depending on the marker analysed, no or low intratumour heterogeneity among three tumour blocks for POLE and CTNNB1 mutations, and p53, MMR and L1CAM expression (range of concordance rate: 92-100%). Similarly, previous studies showed that the molecular analysis on endometrial cancer preoperative specimens are concordant with final hysterectomy specimens obtained at definitive surgical staging [10, 2931]. The intratumour heterogeneity in our study affected the integrated molecular risk assignment in only five cases.…”
Section: Discussionsupporting
confidence: 82%
“…This series of 49 cases showed, depending on the marker analysed, no or low intratumour heterogeneity among three tumour blocks for POLE and CTNNB1 mutations, and p53, MMR and L1CAM expression (range of concordance rate: 92-100%). Similarly, previous studies showed that the molecular analysis on endometrial cancer preoperative specimens are concordant with final hysterectomy specimens obtained at definitive surgical staging [10, 2931]. The intratumour heterogeneity in our study affected the integrated molecular risk assignment in only five cases.…”
Section: Discussionsupporting
confidence: 82%
“…26,27 We should note that endometrial carcinomas are uniform, with respect to genetic events that occur early during oncogenesis, such as MMR loss, POLE mutation, or TP53 mutation. 26,28 Thus, endometrial biopsy or curettings can predict genomic subtypes of endometrial cancer more accurately than grade. Genetic analysis may figure out the tumor heterogeneity and overcome the lack of correlation between biopsy sample and final specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically relevant information about an individual’s tumor could guide surgical urgency and aggressiveness, fertility or hormonal function sparing management options, adjuvant therapy, and/or surveillance schedules. We have demonstrated high concordance between ProMisE molecular classification in diagnostic vs. final hysterectomy samples, far superseding concordance of grade, or histotype as assigned on original pathology reports or within or between reviews by expert gynecologic cancer pathologists [80]. The Leiden team has also shown high concordance of molecular tumor alterations between pre-operative curettage specimens and final hysterectomy specimens (13 gene panel and MSI assay) [81] and a multicenter, prospective trial in Holland is in process to see if surgical management can be improved [82].…”
Section: A New Genomic Era: Molecular Classification Of Endometrial Cmentioning
confidence: 99%
“…However, in the cases examined, although single nucleotide variations and copy number analysis revealed some diversity between anatomic sites within an individual (at time of diagnosis) the ProMisE molecular subgroup categorization was concordant across all tumor sites (6–14 anatomic sites examined per individual) [114]. We have reported on a case of discordant ProMisE categorization between a diagnostic endometrial biopsy and final hysterectomy specimen in an individual with a dedifferentiated endometrial carcinoma [80]. This was secondary to concurrent low grade and high grade areas within the endometrium and myometrium where mismatch repair profiles differed.…”
Section: Rare Histotypes and Diversity Within Tumorsmentioning
confidence: 99%